2020
DOI: 10.1177/2515690x20960644
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Court-Type Thai Traditional Massage Versus Senokot Treatment on Chronic Constipation: A Randomized Controlled Trial

Abstract: Chronic constipation is the disturbances of intestinal motility which is a challenge in primary healthcare around the world. In this study, Court-type Thai traditional massage and Senokot, treatments were assessed and compared in terms of their efficacy in relieving constipation. Forty subjects diagnosed with constipation were recruited and randomized into the massage group and drug group. For 7 days, Thai traditional abdominal massage was provided regularly for the patients in the massage group, while the dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…It was demonstrated that abdominal massage can effectively stimulate intestinal peristalsis and improve intestinal dynamics, thus increasing the frequency of defecation and alleviating difficulty in defecation. Boonruab et al [ 33 ] showed that there was no significant difference in terms of defecation frequency between massage therapy and Senokot therapy in statistical analysis, but the stool properties of massage therapy were better than those of Senokot therapy, and massage therapy led to more continuous defecation management, with an ideal defecation frequency reaching 75%, while the ideal defecation frequency of Senokot group was only 25%. Consideration may be given to the influence of the medication factor in Senokot therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that abdominal massage can effectively stimulate intestinal peristalsis and improve intestinal dynamics, thus increasing the frequency of defecation and alleviating difficulty in defecation. Boonruab et al [ 33 ] showed that there was no significant difference in terms of defecation frequency between massage therapy and Senokot therapy in statistical analysis, but the stool properties of massage therapy were better than those of Senokot therapy, and massage therapy led to more continuous defecation management, with an ideal defecation frequency reaching 75%, while the ideal defecation frequency of Senokot group was only 25%. Consideration may be given to the influence of the medication factor in Senokot therapy.…”
Section: Discussionmentioning
confidence: 99%
“…the abdominal massage improved the chronic constipation by increasing frequency of defecations and sensation of complete evacuation suggested that abdominal massage leading to abdominal cavity pressure change by the relaxation of muscles and ligaments which affect and control abdominal pressure and also affect colon movement, which is the main factor in the defecation process. 25 The lower urinary tract relaxation and increase bladder power after massage session may the major role of LUTS improvement. The adverse event of the massage was not found in the medical records of participants in a Thai traditional massage group.…”
Section: Discussionmentioning
confidence: 99%